GROUNDWATER VULNERABILITY MAPPING ASSESSMENT IN MINGGIR SUBDISTRICT OF SLEMAN YOGYAKARTA SPECIAL PROVINCE, INDONESIA - , Oudone, Phetvilay ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Minggir area is located at the sleman district of Yogyakarta Special Region. The use of chemical fertilizer and pesticide in the agricultural area and the onsite sanitation system used by settlement in the research area can lead to effect on groundwater quality and possibility of percolation and diffusion of contaminants from the ground surface into groundwater. This study has been conducted with two main objectives. The first objective is to assess groundwater vulnerability in the research area by using three different methods. They are GOD method, SVV method and DRASTIC method. The second objective is to determine the powerful groundwater vulnerability method in the research area by comparing groundwater vulnerability map, land use map, and groundwater quality in the research area. Therefore, all important parameters have to be collected both from previous research and field investigation data such as geology, hydrogeology, hydrology and survey of pollution sources location. Then the parameters were preceded and analyzed to build the intrinsic vulnerability maps. The result of research show the degree of intrinsic vulnerability of groundwater in the study area ranges from None to Extreme for GOD method and Very Low to Very High for SVV method, while DRASTIC method response from Low to High classes. The actual nitrate concentration in groundwater and conduct condition indicates that SVV and GOD Methods have drawn more realistic result than DRASTIC method in predicting groundwater contamination risk. Finally, we can conclude that very high vulnerability zone has correlation with nitrate content in groundwater > 50 mg/L. while high vulnerability zone relate to nitrate concentration in groundwater from 10 â 50 mg/L and low vulnerability zone show nitrate concentration in groundwater less than 10 mg/L (< 10 mg/L).